How to thrive in the virtual workplace : simple and effective tips for successful, productive, and empowered remote work - Glazer, Robert (CEO); Sloan, Mick (Simple Truths, 2021)
"As the corporate world continues to embrace virtual offices and working remotely, there is a need for companies to understand how they can intentionally build a remote workforce that thrives. This book serves as a quick guide with actionable steps to take if you are transitioning to a remote workplace or looking to improve your existing setup"--